RISIKO KREDIT DAN MODAL SEBAGAI MODERASI LIKUIDITAS TERHADAP PROFITABILITAS BANK - warmana, oka; Suarjana, Wayan; Martini, Budi (Journal of Applied Management and Accounting Science, 2024)
Profitability is one measure of bank health. However, banks are required not only to pursue profitability but also to be careful in managing risks. Banks must maintain liquidity in order to fulfill their obligations. Credit and capital risks are related to bank liquidity. The higher the credit risk, the bank needs to provide reserve funds. When liquidity decreases, it can be increased with additional capital. This research looked at 45 commercial banks operating in Indonesia in the 2017-2022 period. Interaction term is measured by the absolute difference of variables. The test results show that there is a trade-off between liquidity and profitability, especially in banks with high capital.).